Perceived utility of community notification for sexually violent persons (SVP) on supervised release - Subramanian, Lakshmi (Psychology, crime & law, 2025)
Individuals committed under Sexually Violent Person (SVP) laws can be afforded conditional or supervised release (SR) in the community. SR placement is preceded by community notification. The objectives of this study were to assess SR residents’ attitudes toward community notification and their adverse experiences at being subjected to it. Interviews were conducted with 80 SR residents. In contrast to similar samples, participants presented with an overall favorable attitude toward community notification with a majority of participants rating it as fair and having some utility in reducing sexual offending. Threats/ridicule, job loss, and property damage were the top three adverse experiences reported; however, compared to other samples, participants reported significantly lower rates of job loss, property damage, and physical harm. Potential reasons for participant ratings and experiences as well as differences in ratings across similar samples are discussed.